Assessment of Medication Use by Publics in Sulaimani Province - Enayat, Kamal Aziz; Hama Salih, Mariwan Abdulla; Babakir-Mina, Muhammed (Kurdistan Journal of Applied Research, 2020)
Drug uses is a multi-step process starting from consulting doctor, prescribing, ordering and using via individual either public or healthcare staff for therapeutic reasons. This process can be problematic for several reasons, especially in developing countries due to easily access to medications, self-diagnosis and people recommendation for certain cases. The aims of the present study were to assess the practice and attitude of medication uses and the knowledge about medication advantage and their risks by publics in Sulaymaniyah province. Then to build correlations between demographic characteristics and medication uses, in order to show the main impact of widely used medication on public health status. Finally, to provide community with statistical data about the level of knowledge, attitude and practice KAP in this region. The overall six hundred participant from the average of ten locations between governmental and privates hospitals and pharmacies as well as clinics were selected from central city and towns for data collection. The majority of participants were public from different background. The present study concluded that the 60 percentage of the participant were lack of adequate knowledge about the ability for differentiation between analgesic and antibiotic medications. The results of the current study showed inappropriate practices and attitudes that contribute to increasing health risks. It is also found that 72 percentage of participant who use prescription only drugs such as antibiotics can be possibly stopped after situation disappeared. This study also investigated several reasons for inappropriate practice, such as wrong believes with irregular consumption of medications, illiteracy, poor health services in terms of pharmacies and healthcare staff as well as easy access to most of the types of medications. Therefore, effort by governmental authorities is urgent toward reducing the risk of the situation, and negative consequences regarding inappropriate practice toward patient care in the region.